(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
For the fabrication of engineering components, 3D printing has proven to be a feasible technology because it is an additive process, unlike previous manufacturing methods. The advantages of 3D printing for industrial use include little material wastage, simple manufacturing, minimal human participation, minimal post-processing, and energy efficiency. The advantage and disadvantage of various 3D printing techniques are covered in the study. There is a detailed explanation of various materials that work with each sort of 3D printing procedure. The report also lists the many contexts in which each process type is applied. The research on literature showed that even if the fields of 3D printing have advanced significantly, there are a problems that required to solve, like material incompatibility and material cost. In future, this could be done to improve the procedures and adapt them to work with a variety of materials. More effort must be put into creating affordable printing technologies and materials, that work with these printers because 3D printed products have a wider range of uses.